The Deubiquitinating Enzyme MrUbp14 Is Involved in Conidiation, Stress Response, and Pathogenicity in Metarhizium robertsii - Wang, Zhangxun; Chen, Hua; Li, Hao; Chen, Hanyuan; Huang, Bo (Frontiers in Fungal Biology, 2022)
Protein ubiquitination, which is involved in various biological processes in eukaryotic cells, is a reversible modification of proteins. Deubiquitinases can maintain ubiquitin homeostasis by removing ubiquitin or modulating protein degradation via the ubiquitin-proteasome system (UPS). Metarhizium robertsii, an entomopathogenic fungus, has become a model fungus for investigating the interactions between insects and fungal pathogens. To explore the possible effects of the deubiquitination process on the development, stress response, and virulence of M. robertsii, disruption of MrUbp14 (an ortholog of the yeast ubiquitin-specific protease gene, Ubp14) was performed. The results of this study showed that the deletion of MrUbp14 led to accelerated conidial germination, reduced conidial yields, and decreased expression levels of some genes involved in conidiation. Furthermore, the MrUbp14 mutant (ΔMrUbp14) exhibited decreased tolerance to cell wall-damaging stressors (Congo red and SDS) and heat stress. Importantly, the results of the bioassay demonstrated that the fungal virulence of the ΔMrUbp14 strain was largely reduced in cuticle infection, but not in direct injection, which was accompanied by a significant decline in appressorium formation and cuticle penetration. Moreover, our results demonstrated that the disruption of MrUbp14 resulted in significantly increased ubiquitination levels of total protein, suggesting that MrUbp14 acts as a deubiquitinating enzyme in M. robertsii. In summary, our phenotypic changes in the gene disruption mutants suggest that MrUbp14 is important for conidiation, stress response, and fungal virulence in M. robertsii.